Prevalence and predictors of gender-based violence among Wolkite University female students, southwest Ethiopia, 2021: Cross-sectional study - Workye, Haile; Mekonnen, Zebene; Wedaje, Wesen; Sitot, Aregash (Frontiers in Reproductive Health, 2023)
Background Gender-based violence is an important topic that needs to be taken into account when identifying gender-related gaps and disadvantages that a person might face because of their gender. Violence against women could result in psychological and physical adverse outcomes. Therefore, this study aims to assess the prevalence and predictors of gender-based violence among female students at Wolkite University, southwest Ethiopia, 2021. Method An institutional-based cross-sectional study was conducted among 393 female students and the students were selected by using a systematic sampling method. Data were checked for completeness and entered into EpiData version 3.1 and then exported to SPSS version 23 for further analysis. Binary and multivariable logistic regressions were employed to determine the prevalence and predictors of gender-based violence. The adjusted odds ratio (AOR) with its 95% confidence interval (CI) at a p-value of ≤0.05 was used to check statistical association. Result In this study, the overall prevalence of gender-based violence among female students was 46.2%. The prevalence of physical violence and sexual violence was 56.1% and 47.0%, respectively. Factors that were significantly associated with gender-based violence among female university students were: being a 2nd-year student or having a lower educational level [AOR = 2.56 (95% CI, 1.06–6.17)], being married or living with a male partner [AOR = 3.35 (95% CI, 1.07–10.5], having a father with no formal education [AOR = 15.46 (95% CI, 5.204–45.39)], having a drinking habit [AOR = 2.53 (95% CI, 1.21–6.30)] and not being able to freely discuss issues with their families [AOR = 2.48 (95% CI, 1.27–4.84)] Conclusions and recommendations The result of this study showed that more than one-third of the participants were exposed to gender-based violence. Thus, gender-based violence is an important topic deserving of more consideration; further investigations are important to decrease gender-based violence among university students.